A previously uncharacterized Factor Associated with Metabolism and Energy (FAME/C14orf105/CCDC198/1700011H14Rik) is related to evolutionary adaptation, energy balance, and kidney physiology - Petersen, Julian; Englmaier, Lukas; Artemov, Artem V; Poverennaya, Irina; Mahmoud, Ruba; Bouderlique, Thibault; Tesarova, Marketa; Deviatiiarov, Ruslan; Szilvásy-Szabó, Anett; Akkuratov, Evgeny E; Pajuelo Reguera, David; Zeberg, Hugo; et al. (Nature communications, 2023)
In this study we use comparative genomics to uncover a gene with uncharacterized function (1700011H14Rik/C14orf105/CCDC198), which we hereby name FAME (Factor Associated with Metabolism and Energy). We observe that FAME shows an unusually high evolutionary divergence in birds and mammals. Through the comparison of single nucleotide polymorphisms, we identify gene flow of FAME from Neandertals into modern humans. We conduct knockout experiments on animals and observe altered body weight and decreased energy expenditure in Fame knockout animals, corresponding to genome-wide association studies linking FAME with higher body mass index in humans. Gene expression and subcellular localization analyses reveal that FAME is a membrane-bound protein enriched in the kidneys. Although the gene knockout results in structurally normal kidneys, we detect higher albumin in urine and lowered ferritin in the blood. Through experimental validation, we confirm interactions between FAME and ferritin and show co-localization in vesicular and plasma membranes.
Keywords: Body Weight; Animals; Ferritins; Kidney; energetický metabolismus; tělesná hmotnost; lidé; Neanderthals; zvířata; neandertálci; Genome-Wide Association Study; ledviny; Energy Metabolism; celogenomová asociační studie; ferritiny; Humans